Coral reef socio-ecological systems analysis & restoration - Uribe-Castañeda, Natalia (2018)
Restoration strategies for coral reefs are usually focused on the recovery of bio-physical characteristics. They seldom include an evaluation of the recovery of the socio-ecological and ecosystem services features of coral reef systems. This paper proposes a conceptual framework to address both the socio-ecological system features of coral reefs with the implementation of restoration activity for degraded coral reefs. Such a framework can lead to better societal outcomes from restoration activities while restoring bio-physical, social and ecosystem service features of such systems. We first developed a Socio Ecological System Analysis Framework, which combines the Ostrom Framework for analyzing socio-ecological systems and the Kittinger et al. human dimensions framework of coral reefs socio-ecological systems. We then constructed a Restoration of Coral Reef Framework, based on the most used and recent available coral reef restoration literature. These two frameworks were combined to present a Socio-Ecological Systems & Restoration Coral Reef Framework. These three frameworks can be used as a guide for managers, researchers and decision makers to analyze the needs of coral reef restoration in a way that addresses both socio-economic and ecological objectives to analyze, design, implement and monitor reef restoration programs.